Regulation of the ER stress response by a mitochondrial microprotein - Qian Chu; Thomas F. Martinez; Sammy Weiser Novak; Cynthia J. Donaldson; Dan Tan; Joan M. Vaughan; Tina Chang; Jolene K. Diedrich; Leo Andrade; Andrew Kim; Tong Zhang; Uri Manor; et al. (Nature Communications, 2019)
Cells trigger an unfolded protein response (UPR) in the endoplasmic reticulum, but its regulation by mitochondria is unclear. Here, the authors report a 54-residue microprotein PIGBOS that participates in inter-organelle contact between the endoplasmic reticulum and the mitochondria and may regulate UPR.